2012
DOI: 10.1016/j.ygeno.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of transducin subunit gene families in early vertebrate tetraploidizations

Abstract: Hundreds of gene families expanded in the early vertebrate tetraploidizations including many gene families in the phototransduction cascade. We have investigated the evolution of the heterotrimeric G-proteins of photoreceptors, the transducins, in relation to these events using both phylogenetic analyses and synteny comparisons. Three alpha subunit genes were identified in amniotes and the coelacanth, GNAT1-3; two of these were identified in amphibians and teleost fish, GNAT1 and GNAT2. Most tetrapods have fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…However, searches in species that evolved before the divergence of tunicates were unfruitful. These findings are consistent with previous studies (Lagman et al, 2012) and illustrate that the Gc gene repertoire is limited only to GNG-and GNG13-like genes in most analyzed metazoans that evolved before the divergence of deuterostomes. Later, the GNG gene cluster and the ancestral gene of the transducin family likely expanded in the two genome doublings, i.e.…”
Section: Evolution Of Gc Families Within Holozoanssupporting
confidence: 93%
See 2 more Smart Citations
“…However, searches in species that evolved before the divergence of tunicates were unfruitful. These findings are consistent with previous studies (Lagman et al, 2012) and illustrate that the Gc gene repertoire is limited only to GNG-and GNG13-like genes in most analyzed metazoans that evolved before the divergence of deuterostomes. Later, the GNG gene cluster and the ancestral gene of the transducin family likely expanded in the two genome doublings, i.e.…”
Section: Evolution Of Gc Families Within Holozoanssupporting
confidence: 93%
“…S4b). Although, phylogenetic trees lacked high confidence support, the finding that bilaterian invertebrate sequences are more GNAI-like is strongly supported by previous studies that demonstrated the transducins (GNAT family belonging to Gai/o class) likely evolved at the early origins of vertebrates and are involved in phototransduction in the rod and cone photoreceptor cells of the vertebrate retina (Lagman et al, 2012;Lamb, 2009;Larhammar et al, 2009;Lin et al, 2013). Furthermore, our phylogenetic analysis also shows that GNAO-like amino acid sequences are found in almost all analyzed metazoans.…”
Section: Evolution Of Ga Families Within Holozoansmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, most phylogenetic analyses -including analysis of Hox sequences [23][24][25][26] -do not support the hypothesis that the Latimeria genome is slow evolving, i.e. they do not place coelacanth sequences on short branches nor do they detect low substitution rates [24,[27][28][29][30][31]. The clearest example, which involves the largest number of genes, is a phylogeny based study of forty-four nuclear genes that does not show a dramatic decrease, if any, in the rate of molecular evolution in the coelacanth lineage [32].…”
Section: Low Molecular Diversity and Low Geographic Differentiation Imentioning
confidence: 98%
“…4 Another presentation reported on studies of the evolution of visual opsin genes in relation to early vertebrate tetraploidizations in a manner similar to what has been done for other gene families in the phototransduction cascade. 5 Two new techniques were presented: (i) live tracing of cell lineages using a Cre-reporter line with improved optical properties (contact person: Bettina Ryll at bettina .ryll@ebc.uu.se) and (ii) a rapid whole mount in situ and immuno-hybridization technique to be used in automated screens (contact person: Nina Kaukua at nina.kaukua@ki.se).…”
mentioning
confidence: 99%